Bibliometric Analysis of Comparative Studies in Mathematics Textbook Analysis Research: Trends, Gaps, and Future Directions (Mark Revision Manuscript) - Kristanto, Matias Vico Anggoro; Nurhasanah, Farida; Setiawan, Rubono (Universitas Muhammadiyah Mataram, 2025)
While the cross national comparative analysis of mathematics textbooks is an expanding field of research, a dedicated bibliometric mapping to identify research gaps and provide clear directions for future inquiry is notably absent. Therefore, this study aims to provide a bibliometric analysis that maps publication trends, identifies the most influential authors and documents, and delineates research gaps to offer clear signposts for future research. The methodology involves a qualitative analysis and mapping of data retrieved from the Scopus database for the period 2010–2024. Following a screening process based on inclusion and exclusion criteria, a final corpus of 89 papers was selected for synthesis in this study. The analysis software, VOSviewer, was employed for keyword co-occurrence and co-citation mapping, supplemented by distribution diagrams for trend analysis. Four main findings emerged: first, there has been a significant and increasingly multidisciplinary growth in publications. Second, a thematic evolution is observed, shifting from structural reviews towards more complex evaluative approaches focused on cognitive load and learning implications. Third, research gaps were identified concerning the linguistic presentation of mathematical concepts and the inclusion of social values. Finally, the analysis highlights the most influential authors and articles in the field. Implications of this study are expected to serve as a compass for researchers, guiding them toward achieving novelty in future comparative analyses of mathematics textbooks.